2005
DOI: 10.1192/bjp.187.3.209
|View full text |Cite|
|
Sign up to set email alerts
|

Substance use disorders and the orbitofrontal cortex

Abstract: The orbitofrontal cortex has an important role in addictive behaviours. Further studies are needed to elucidate the underlying neuronal substrates of cue reactivity, craving and decision-making, and the implications for treatment and relapse prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(74 citation statements)
references
References 88 publications
6
66
2
Order By: Relevance
“…For instance, it is possible that the causal direction flows from substance use behaviors to reduced trait mindfulness tendencies. In particular, because trait mindfulness involves the use of higher order cognitive processes (Ives-Delliperi et al, 2011), it is possible that higher levels of substance use behaviors reduce trait mindfulness by impairing higher order cognitive processes (Dom et al, 2005). Moreover, it is also possible that the negative trait mindfulness-substance use behaviors relationship is reciprocal, such that trait mindfulness is associated with a small degree of protection again substance use behavior (Marlatt, 2004) and substance use behaviors reduce trait mindfulness (Dom et al, 2005; Ives-Delliperi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it is possible that the causal direction flows from substance use behaviors to reduced trait mindfulness tendencies. In particular, because trait mindfulness involves the use of higher order cognitive processes (Ives-Delliperi et al, 2011), it is possible that higher levels of substance use behaviors reduce trait mindfulness by impairing higher order cognitive processes (Dom et al, 2005). Moreover, it is also possible that the negative trait mindfulness-substance use behaviors relationship is reciprocal, such that trait mindfulness is associated with a small degree of protection again substance use behavior (Marlatt, 2004) and substance use behaviors reduce trait mindfulness (Dom et al, 2005; Ives-Delliperi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, what are the mechanisms behind the behavior to use the Internet again and again, although a person explicitly knows that he/she will experience negative consequences in the long run? Do they have a myopia for the future or is the reaction to the Internet-related stimuli so strong that they experience cue-reactivity and craving, as it is well-known from substance dependency (e.g., Grant et al, 1996; Anton, 1999; Childress et al, 1999; Tiffany and Conklin, 2000; Bonson et al, 2002; Brody et al, 2002, 2007; Franken, 2003; Dom et al, 2005; Heinz et al, 2008; Field et al, 2009)? We will focus on these neuropsychological mechanisms potentially contributing to the loss of control in the next sections.…”
Section: Generalized and Specific Internet Addictionmentioning
confidence: 99%
“…For example, imaging studies of addicts have consistently revealed abnormalities in blood flow in the OFC [28][29][30][31][32][33] (for an excellent review, see [34]). Alcohol and cocaine addicts display reductions in baseline measurements of OFC activation during acute withdrawal and even after long periods of abstinence.…”
Section: Addictive Behavior and Outcome Expectanciesmentioning
confidence: 99%